Effect of Spontaneous Delivery and Elective Caesarean Section on Number of Bifidobacterium Colony in Newborns - Engga L. Erwanto (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To know the effect of vaginal delivery and elective caesarean section in total colony of bifidobacterium in newborn’s faeces. Method: All the research subject who has fulfilled the inclusion criteria, the newborn’s faeces taken on the 3rd to 4th day after delivery. One cc of faeces diluted into 9 cc thioglycolate in a sterile tube and sent to the Microbiology Laboratory of Hospital of Dr. M. Djamil Padang for the examination of colony of bifidobacterium. Data was processed and analized statistically. Result: The sample was taken from 41 research subject of vaginal delivery and 41 research subject of elective caesarean section. The average of total colony of bifidobacterium in newborn’s faeces with vaginal delivery is 23,588,220 CFU/gram and the average of total colony of bifidobacterium in newborn’s faeces with elective caesarean section is 4,151,829.3 CFU/gram. Conclusion: Total colony of bifidobacterium in newborn’s faeces with vaginal delivery is higher than elective caesarean section, and proved statistically significant (p < 0.05). [Indones J Obstet Gynecol 2011; 35-2: 49-52] Keywords: bifidobacterium, vaginal delivery, caesarean section